Use the Standard Library - Dennison, Justin; Spurgin, Aubri (Packt Publishing, 2024)
Unlock the full potential of Python by mastering its Standard Library with this comprehensive course. Designed for developers aiming to streamline their coding process, the course begins with an introduction to the Python Standard Library, detailing its purpose and access methods. You'll explore a vast array of built-in modules that simplify various programming tasks. Starting with fundamental modules like os and os.path, you'll learn to interact with the operating system and manipulate file paths through practical examples. You'll perform file system operations, navigate directories, and handle paths efficiently. Progressing further, you'll master the datetime module, covering operations involving date and time, such as arithmetic, comparisons, parsing, and timezones-crucial skills for applications relying on time-based data. The course also delves into the math module for advanced mathematical operations and the sys module for insights into the Python interpreter's settings, runtime environment, and module management. Additionally, you'll learn to use the random module to generate random numbers, essential for simulations, testing, and security applications. By the end of this course, you'll be proficient in using Python's Standard Library to enhance your development efficiency and effectiveness.
Online resource; title from title details screen (O'Reilly, viewed June 24, 2024)
Keywords: Python (Computer program language); Application software -- Development; Python (Langage de programmation); Logiciels d'application; Développement; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet